Economically sustainable shade for feedlot cattle in Brazil - Maia, Alex S.C. [UNESP]; Moura, Gustavo A.B. [UNESP]; Pacheco, Rodrigo; Milan, Hugo F.M. [UNESP]; Neto, Marcos Chiquitelli; Fonsaca, Vinicius F.C. [UNESP]; Gebremedhin, Kifle G. (American Society of Agricultural and Biological Engineers (ASABE), 2022)
The positive effect of shade on animal welfare is widely known, but the literature lacks data on the magnitude of its economic impact. In this study, we tested the hypothesis that a well-designed shade structure is economically sustainable for feedlot cattle in Brazil. In the summer of 2020, a total of eight hundred B. indicus × Bos Taurus steers were randomly assigned in (a) eight soil-surfaced pens with shade from a longitudinal galvanized steel-roofed structure with north-south orientation (2.7 m2 of shade/animal) or (b) eight soil-surfaced pens without shade. Our results show that around noon of very hot days (days with mean solar radiation above 650 W m-2 and mean air temperature above 33 ºC), feedlot cattle in shaded pens spent 80% of their time in shade, reduced water intake (-5.5 L animal-1) and presented significantly lower heat stress indicators (by 5 ºC for body-surface temperature, 1 ºC for subcutaneous temperature, and 10 breaths min-1 for respiration rate). Although dry matter intake was similar (P = 0.6805) between treatments, cattle in shaded pens presented higher average daily gain and hot carcass weight was 8 kg animal-1 heavier (P = 0.0002). Considering an initial investment of $90/animal for a structure lasing 15 years, the expected payback time, based on the net present worth, was predicted to be four finishing cycles (~110 days per cycle). In conclusion, this study confirms that a well-designed shade is a feasible environmental management strategy that improves performance, welfare and profitability of feedlot operations in Brazil.
Keywords: Cattle; Shade; Sustainability; Tropical Environment